Gambaran Pengelolaan Sampah di Pondok Pesantren Darul Muhtadin Kota Jambi - Siahaan, Sondang; Fauziah, Rina; Supriatna, Supriatna; Novitasari, Jessy (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Waste is the solid residue of daily human activities or natural processes. Waste management is a form of environmental education that can raise awareness of the importance of protecting the environment and carrying out good waste management. The purpose of this study was to determine the description of waste management at the Darul Muhtadin Islamic Boarding School in Jambi City. The scope of this study is waste management at the Darul Muhtadin Islamic Boarding School in Jambi City, which includes the amount of waste generation, waste sorting, waste packaging, waste collection, waste transportation, and waste storage. This research is quantitative, and the research design used in this study is descriptive by means of direct observation and interviews. The results of the research at the Darul Muhtadin Islamic Boarding School in Jambi City show that 50% of the time there is a trash can at the location of the source of waste, 100% of waste sorting is not carried out in waste management, 100% of waste containers do not meet health requirements in waste management, 50% of waste collection does not meet health requirements in waste management, 75% of waste transportation does not meet health requirements in waste management at the boarding school, and 25% of waste containment places in their location and buildings do not meet the requirements, namely less than 30 meters in waste management at the boarding school.